Epidemiologia, controle químico e distribuição espacial de Sclerotinia sclerotiorum em Mato Grosso - Giachini, Roseli Muniz (2013)
In soybean, the white mold, caused by S. sclerotiorum, which has always been sporadic in areas of soybean cultivation in the state of Mato Grosso, there were problems caused by the 2008/09 as occurred in small foci, with few infected plants per hectare. A number of factors such as monoculture, crop succession with highly susceptible species and planting of infected seed, caused the disease became a major problem, with significant losses in soybean yield. Thus, the aim of this work was to study S. sclerotiorum and the factors that influence its growth. Thus, it was verified (1) biometrics and germination of sclerotia, (2) and detection of the pathogen inoculation of seeds, (3) the sensitivity of the sclerotia fungicides, (4) growth and development of the pathogen as a function of temperature and water availability, and (5) the spatial distribution of S. sclerotiorum. The length, width and thickness of sclerotia in soybean varies from 2.41 to 13.62 mm, 2.06 to 3.46 mm 1.58 to 2.38 mm, respectively. The most appropriate means of inoculation in soybean seeds is the Potato Dextrose Agar without fluid restriction. The most effective period for inoculation is 72 hours. The paper roll method allowed the detection faster and more efficient pathogen in batches of seeds with 5% contamination. Fungicides have efficiency in reducing white mold, even with just one application. The effect of fungicide application on soybean on germination of sclerotia and apothecia formation occurs up to 50 days of incubation of sclerotia. Soil moisture affects the germination carpogenic, the number of apothecia produced by sclerotia, mass, length and diameter of the apothecia. The spatial variation of S. sclerotiorum occurred in foci.